Conflict Communication in Marriage Indonesia Minangkabau Matrilineals’ Culture Women with Malay Patrilineals’ Culture Men in Medan, Indonesia - Beydha, Inon (2007)
We are living in a “global village”, and for this reason, there is more need than ever to help people communicate more effectively, and to understand conflict communication and how to manage it, especially in intercultural marriages that pose a unique opportunity to study about it. The purpose of this study was to understand the phenomenon of the conflict communication in intercultural marriage faced by the Indonesia Minangkabau matrilineals’ culture women with patrilineals’ culture Malay men. This study explained the meaning of the conflict to answer the research questions. The research questions of this study are: 1) how the phenomenon and effect of the conflict in the intercultural marriage faced by the Indonesia Minagkabau matrilineals’ culture women who are married with Malay patrilineals’ culture Men, 2) what the sources of the intercultural marital conflict, and 3) how the strategies of conflict communication management that use by the Indonesia Minangkabau matrilineals’ culture women in their intercultural marriage ? The data collection method was phenomenology qualitative research and consisted of in-depth interviews to understand and explain the experiences of the conflict communication management in the intercultural marriage among Indonesia Minangkabau matrilineals’ culture women with Malay patrilineals’ culture men. The respondent who were involved in being consist of six Indonesia Minangkabau matrilineals’ culture women who willingly were prepared to share their experiences. They had the experiences as the wive of Malay patrilineals’ culture men between two to eight years. Each of in-depth interview was recorded by using recording tape and transcribed verbatim to find the themes and categorizes for answer the research questions that based on topic by being arranged and through. Each themes was analyzed to identify common themes and findings, which were presented as results. The findings indicate that phenomenon of intercultural marital conflict was natural. The effect of the intercultural maritals’ conflict had two categories: 1) positive and constructive, and 2) negative and destructive. The positive effect of the intercultural maritals’ conflict had three categories: 1) the satisfied marriage, 2) the families’mental health, and 3) the global unity and harmonious. The negative effect of the intercultural maritals’ conflict had five categories: 1) divorce, 2) un-satisfied marriage, 3) the families’ mental health problem, 4) the stereotype and prejudice among the intercultural relationship, and 5) the global dispute. The sources of the intercultural maritals’ conflict insists of three categories: 1) the differences of the values’ culture and the obstacle of the culture used, 2) the differences of the communication context and the un-effective of the communication, 3) the stereotype and prejudice that exist as the marital conflict foundation. Hence of the strategy to manage conflict communication in intercultural marriage were: 1) be patient or accommodating (obliging), 2) Bamufake jo sumando (negotiation with the husband), and 3) Bamufake jo dunsanak dan ninik mamak (mediation or third party help). Finally, the study success to build the model of conflict communication management in marriage among Indonesia Minangkabau matrilineals’ culture women with Malay patrilineals’ culture Men.